Developing text-based measurable reliability factors for islamic websites - Muhammed Nasser, Rasheed; Mahmud, Murni (IIUM Press, International Islamic University Malaysia, 2017)
This book tried to develop factors based on Islamic literature that bring reliability to Islamic website. Islamic authors always refer to Quran and Sunnah (Hadith, Sirat, and Mathahib) as well as scholars’ says to increase the reliability of any religious content (Al-graitely, 2009; Al-tablawi, 2007; Al-tiwajri, 2013; Aqeeb, 2011). It is commonly known that any Islamic content to be acceptable should be supported by evidences from Quran and Sunnah and/or scholars’ says. Apart, an empirical approach to assess reliability of Islamic website is necessary. Even though there are some tools developed to assess the reliability of websites for domains such as healthcare, search engine result and ecommerce (Kc, 2009; Knight & Burn, 2005; Tanaka et al., 2010; Wang & Liu, 2007), those cannot be adopted completely with Islamic website because it is always better to assess the quality of information in its context (Knight & Burn, 2005). Therefore, this study has targeted to develop and assess reliability factors of Islamic websites that can be used to develop empirical tool